2021
DOI: 10.1002/jcop.22646
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the knowledge and awareness of pediatric residents and pediatricians about autism spectrum disorder at a single center in Turkey

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder and pediatricians play a critical role in early diagnosis. This study was conducted to evaluate the knowledge, beliefs, and experiences of pediatric residents and pediatricians about ASD. A 35‐item questionnaire consisting of two sections was administered. The diagnostic features section consisted of questions measuring the level of knowledge about diagnostic criteria of ASD. The general knowledge and beliefs section consisted of questions about b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(27 reference statements)
2
8
0
Order By: Relevance
“…Approximately two-thirds of the participants (67.2%) selfreported that they did not have enough experience with ASD. This result is consistent with the results of Austriaco et al 16 and Citil et al 10 which shown that paediatricians experience discomfort in the field. Although these data suggest that paediatricians have more experience in the field, the sense of competence is limited as it is evaluated subjectively and can be reconsidered in studies where competence is evaluated objectively.…”
Section: Autism Related Experience and Past-trainingsupporting
confidence: 92%
See 1 more Smart Citation
“…Approximately two-thirds of the participants (67.2%) selfreported that they did not have enough experience with ASD. This result is consistent with the results of Austriaco et al 16 and Citil et al 10 which shown that paediatricians experience discomfort in the field. Although these data suggest that paediatricians have more experience in the field, the sense of competence is limited as it is evaluated subjectively and can be reconsidered in studies where competence is evaluated objectively.…”
Section: Autism Related Experience and Past-trainingsupporting
confidence: 92%
“…7-9 Similar results were obtained in studies conducted in our country. [10][11][12] In parallel with the theoretical inadequacy regarding the etiology, symptoms, clinical course, and treatment of ASD, problems are also observed in the screening of ASD and its referral to higher units in clinical practice. While it was found that patients screened for ASD were not adequately referred to higher units, 13,14 a retrospective study conducted with children diagnosed with ASD in our country found that very few children were referred to child psychiatry despite their previous paediatric clinic applications.…”
Section: Introductionmentioning
confidence: 99%
“…25 27 Çitil et al suggested that insufficient knowledge and beliefs about ASD among paediatricians could result in diagnostic and interventional delays in Turkey. 28 Mukhamedshina et al found that primary care paediatricians had difficulties in early identification of ASD and had limited ability to provide ASD knowledge in general in Russia. 17 Our study revealed that a very low percentage of participants correctly knew the main symptoms of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric residents or pediatricians in different countries had different levels of ASD knowledge. However, it is difficult to evaluate which country’s pediatric residents or pediatricians have better ASD knowledge because of the differences in questionnaires and demographic characteristics such as age and gender [ 26 , 29 ]. In addition, child health care workers [ 30 , 31 ], general practitioners [ 32 ], pediatric nurses [ 33 ], psychiatric nurses [ 34 ], rehabilitation therapists [ 35 ] and other professionals [ 36 ], as well as the general public [ 37 ] which include parents [ 38 ] and teachers [ 39 ], lack knowledge and awareness of ASD, which presents a major obstacle to early identification of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Turkish scholars had used self-made questionnaires to investigate 45 pediatricians and 56 pediatric residents about ASD knowledge, beliefs and experiences. The results indicated a lack of awareness and knowledge of ASD among pediatric residents [ 26 ]. Due to the small sample size of this study and the differences in standardized training systems between China and Turkey, the above conclusion may not be applicable to Chinese pediatric residents.…”
Section: Introductionmentioning
confidence: 99%